Design guidelines for online resources: a longitudinal analysis of information processing. (10th June 2016) - Mahony, Carolanne; Sammon, David; Heavin, Ciara
Abstract: This paper proposes that to create superior information resources that meet the information needs of the target audience, a greater understanding of information processing is required. We suggest that the subjective assessment criteria that information-seekers use to process information resources and the information they contain can be used to produce design guidelines for online information resources. This is tested using data from a participant in an eighteen-month longitudinal study of expectant and new mothers. From our participant, three information resource assessment criteria (convenience, credibility, and format) and five information assessment criteria (complete, easy to understand, references, relevance and reliability) were identified. These eight criteria were used to generate design guidelines to meet the needs of our participant. This article provides an analysis tool that can be used by other researchers to collect and analyse subjective assessment criteria.